Problematika Pembelajaran Sejarah Kebudayaan Islam di Madrasah - Kiki Agustinar; Ulva Rahmi; Aisyah Aisyah; Andy Riski Pratama (Concept: Journal of Social Humanities and Education, 2023)
Learning the History of Islamic Culture (SKI) in Madrasahs has the aim of providing knowledge about Islamic history and culture to students, then from this history students are expected to be able to take inspiration, values ​​and meaning in that history. However, in reality, after being investigated, learning the history of Islamic culture in Madrasas found several problems (problematics) in SKI learning. This research aims to find out what the problems are and how to overcome them by using the library research method by reading sources from the internet such as journals which the researchers then analyze. Then the results of this research are that the problems of SKI learning include: problems of students, problems of educators, problems of facilities and infrastructure, problems of insufficient learning time, negative views about SKI, problems of learning that is less interesting or monotonous, and problems of the dominance of cognitive aspects of knowledge. In SKI learning, the solution to overcome this problem is for teachers to better master the learning material and teachers are required to be creative and innovative in creating an SKI learning atmosphere that is interesting and easy to understand by students by using interesting strategies, media and methods using advanced science and technology technology.